Pengaruh Tata Kelola Pemerintahan, Indeks Pembangunan Manusia dan Total Productivity Terhadap Investasi Asing di Indonesia - Desmintari; Aryani, Lina (School of Business, Bogor Agricultural University (SB-IPB), 2022)
One of the factors suspected of playing a positive role in encouraging economic growth is foreign direct investment (FDI). The purpose of this study is to analyze and identify the factors that influence the inflow of foreign capital, especially foreign direct investment into a country in terms of the level of economic progress of the country. This study uses a regression approach, the objects of this study are 5 countries in Asia (China, Japan, India, South Korea and Indonesia). Time series data is used for a period of ten years (2010-2019), while cross section data is used to observe 5 sample countries. The results show that in the first pattern of governance, inflation and exchange rates have no effect on foreign investment flows, while GDP has no effect on foreign investment flows, the second pattern of the human development index has no effect on investment, and the third pattern shows that total productivity factors have no effect. to investment. The conclusion of this study is that there are differences in results in the first pattern, the second pattern and the third pattern. Keywords: government governance, human development index, foreign direct investment, total productivity, gross domestic product